A guide to sustainable consumption - Burja, Alenka (knjige, 2023)
This guide introduces readers to key challenges in five important areas of a consumer’s life that impact the environment the most:food, housing, mobility, household appliances, and household goods. Possible solutions are suggested, recommendations to increasesustainability are outlined, and examples of good practice in Slovenia are given. The guide also uses environmental indicator graphs andvarious diagrams to show the trends in these five topics. When describing these key areas, the guide follows the life cycle phases and theDPSIR concept. The final part of the guide features additional information and links to more in-depth sources.
Keywords: elektronske knjige; Potrošnja; Trajnostna strategija; Vsakdanje življenje